2015
DOI: 10.1310/sci2102-140
|View full text |Cite
|
Sign up to set email alerts
|

Energy Cost of Lower Body Dressing, Pop-Over Transfers, and Manual Wheelchair Propulsion in People with Paraplegia Due to Motor-Complete Spinal Cord Injury

Abstract: Resting VO2 for adults with motor-complete paraplegia is 3.0 mL O2/kg/min, which is lower than standard resting VO2 in able-bodied individuals. Progressively more energy is required to perform MWP, LBD, and POTs, respectively. Use of the standard METs formula may underestimate the level of intensity an individual with SCI uses to perform physical activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
2
1
Order By: Relevance
“…These higher values, compared with our findings, could be explained by the involvement of active movement of the upper body, trunk, and arms (desk work, computer work, reading), in these other studies and differences in study samples. Interestingly, these other studies showed that sitting or working in a sitting position is not or hardly enough to interrupt sedentary behavior (<1.5 METs) in both people with motor-incomplete or motor-complete SCI [15,17,18]. Results from other studies in the general population were in line with our findings and found no significant differences in EE during supine and motionless sitting measurements [30,31].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These higher values, compared with our findings, could be explained by the involvement of active movement of the upper body, trunk, and arms (desk work, computer work, reading), in these other studies and differences in study samples. Interestingly, these other studies showed that sitting or working in a sitting position is not or hardly enough to interrupt sedentary behavior (<1.5 METs) in both people with motor-incomplete or motor-complete SCI [15,17,18]. Results from other studies in the general population were in line with our findings and found no significant differences in EE during supine and motionless sitting measurements [30,31].…”
Section: Discussionsupporting
confidence: 91%
“…There were no differences between the two ambulation groups. Other studies determined EE during activities considered sedentary in motor-complete SCI (or a combination with motor-incomplete) and found higher values between 1.2 and 1.6 METs [15,17,18]. These higher values, compared with our findings, could be explained by the involvement of active movement of the upper body, trunk, and arms (desk work, computer work, reading), in these other studies and differences in study samples.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations